The Intrepid Guerrillas of North Luzon. - Norling, Bernard (JSTOR EBA., 2010)
"Following the Japanese invasion of the islands in 1942, North Luzon was the staging area for several Filipino-American guerrilla bands who sought to gather intelligence and to destroy enemy military installations or supplies. Bernard Norling focuses on the Cagayan-Apayao Forces, or CAF, commanded by Maj. Ralph Praeger. Their bravery was unquestionable, but by September 1943 all but one member of Troop C had been claimed by combat, enemy capture, or disease. The only survivor, Capt. Thomas S. Jones, remembered, ""Defeat is a terrible thing. ... It brings down with it the whole structure abo